Profile of the aging population that looks for the DST and aids reference centerin passos/MG - Souza, Nilzemar R; Bernardes, Elexandra Helena; Carmo, Tânia Maria D; Nascimento, Evania; Silva, Edilaine S; Souza, Bruna NA; Bento, Patrícia de Fátima (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Introduction: sexuality and aging nowadays mean talking about two fascinating themes, but at the same time, it is still full of prejudice and taboos. Sexual feelings, needs and relationships are not a privilege only of young people, and with the increase of life expectancy, brazilian mature people started living this process with greater intensity. Objective: to characterize the profile of the aging population who were assisted in the CTC (Counseling and Testing Center) at a STD/Aids Reference Center from 1992 to 2009 in Passos/MG. Methods: it is a descriptive research with quantitative approach, which oriented the data collection from the consultation of 113 files of elderly people who were assisted since the opening of the Reference Center in 1992 until 2009; the organization was shown in graphs and tables as well as the statistics analysis. Results: the data have shown a predominance of 74,34% masculine elderly people, between 60 to 65 years old (51,33%), 35,40% have finished high school and junior high school, 40,85% are married, 40,70% needed the Reference Center due to the exposition to a risk situation, 71,71% are heterosexuals, and 66,37% have unprotected sexual intercourse. Conclusion: with this profile it is highlighted an increase of risk of contamination and the epidemiological evolution of HIV among the elderly, indicating the necessity of developing preventive actions in STD/aids with this population for a safe and healthy sexual life.